The Impact of Audit Quality on the Cost of Capital: Evidence from Malaysia - Batten, Matthew James (2017)
The aim of this paper is to look at the impact audit quality has on the cost of capital for publically listed companies in Malaysia. This work seeks to expand on previous literature by examining the impact audit quality has on financing costs in a different context to previous studies by looking at a developing country in South East Asia. It is also one of the first papers to use data from the post-financial crisis period. In this study two OLS regressions were run, one for the cost of equity and one for the cost of debt, in order to test for the impact that audit quality had. In line with previous studies the Big 4 auditors were used as proxies for audit quality when included in the regressions. The results showed that higher audit quality had a negative effect on the cost of debt, however no significant relationship was found between audit quality and the cost of equity. These results were robust to whether a Big 4 dummy variable was used or a “Big 3” variable was used. The results would indicate that country specific factors may influence the impact audit quality has, in particular the level of shareholder protection present as well as the litigiousness of the environment.